Method for modifying microspheres by styrene-maleic anhydride copolymer or derivative thereof, microspheres and application thereof

By forming a styrene-maleic anhydride copolymer coating on the surface of microspheres and crosslinking it, the problems of mechanical strength and chemical stability of microspheres were solved, achieving uniform reinforcement and high-density functional group introduction of microspheres, making them suitable for a variety of chromatography media.

CN121495201APending Publication Date: 2026-02-10SAIFEN TECH YANGZHOU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511920273.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-02-10

Smart Images

  • Figure CN121495201A_ABST
    Figure CN121495201A_ABST
Patent Text Reader

Abstract

The invention discloses a method for modifying a microsphere by using a styrene-maleic anhydride copolymer or a derivative of the styrene-maleic anhydride copolymer, the microsphere and application of the microsphere. The styrene-maleic anhydride copolymer or the derivative of the styrene-maleic anhydride copolymer is used as an enhancement and functionalization precursor; the preparation method comprises the following steps: coating internal pores and surfaces of matrix microspheres such as polymethacrylate, polystyrene-divinyl benzene or agarose with the covalently-bonded network-shaped support structure formed on the surface of a microsphere skeleton through an in-situ cross-linking reaction. According to the method, the mechanical strength of the microspheres is remarkably improved, high-density functionalization of the surfaces of the microspheres is synchronously achieved, the enhancement effect is uniform, pore channels are not blocked, and the obtained microspheres have excellent compression resistance, improved chemical stability and rich subsequent coupling reaction sites and are widely applied to preparation of high-performance chromatography packing, adsorbents or drug carriers.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a method for modifying microspheres, in particular to a method for modifying microspheres with styrene-maleic anhydride copolymer or its derivatives, microspheres and their applications. BACKGROUND

[0002] Microspheres, such as polymethacrylate (PMA), polystyrene-divinylbenzene (PS-DVB) and agarose microspheres, are key matrix materials in biopharmaceutical separation (such as chromatography), catalytic carriers and drug delivery systems. However, these matrix microspheres face the following common challenges in practical applications: 1) insufficient mechanical strength: especially soft gel (such as agarose) is prone to compression deformation in high flow rate chromatography, resulting in increased column pressure and decreased column efficiency. 2) surface chemical inertness: the surface of PS-DVB microspheres lacks active functional groups, making it difficult to directly perform biological coupling or functional modification. 3) limited chemical stability: some microspheres swell or degrade in extreme pH or organic solvents, limiting their application range. Existing enhancement methods are mostly physical coating or overall crosslinking, which often leads to microsphere pore blockage, mass transfer efficiency decline, or low and uneven functional group density. SUMMARY

[0003] The purpose of the present application is to provide a method that can uniformly enhance microspheres while maintaining the integrity of the matrix microspheres, and simultaneously introduce high-density reactive functional groups. The present application also provides microspheres prepared by the method and their applications.

[0004] Technical solution: The method uses physical adsorption or chemical reaction to form a coating layer of styrene-maleic anhydride copolymer or its derivatives on the surface of the microspheres, and then uses a crosslinking agent to form a network structure.

[0005] The method comprises the following steps:

[0006] S1: Dissolution of styrene-maleic anhydride copolymer or its derivatives: Dissolve the styrene-maleic anhydride copolymer or its derivatives in an organic solvent, and heat and stir until a uniform transparent solution is formed;

[0007] S2: Wetting of microspheres: Add the matrix microspheres to the solution obtained in S1 and continue stirring;

[0008] S3: Anchoring of styrene-maleic anhydride copolymer or its derivatives: Use physical adsorption or chemical reaction to anchor the styrene-maleic anhydride copolymer or its derivatives on the surface of the microspheres to form a coating layer;

[0009] S4: Solidification of the coating layer: Add a crosslinking agent to the anchored coating layer system to form a crosslinked network support structure;

[0010] S5: Post-processing: Separate the microspheres by filtration or centrifugation, and wash to obtain the modified microspheres.

[0011] Technical Principle: Using low molecular weight styrene-maleic anhydride copolymer (SMA) or its derivatives as a precursor, the solution fully wets the pores of the microspheres. Subsequently, in-situ cross-linking is performed using a cross-linking agent, forming a robust, covalently bonded cross-linked network coating on the surface of the microsphere skeleton and the inner walls of the pores. The SMA or its derivative solution can penetrate deep into the microsphere pores, and the cross-linked coating supports the microsphere skeleton from the inside, rather than merely coating the outer surface. This significantly improves the overall compressive strength without significantly altering the original morphology and pore size distribution of the microspheres. The coating surface is rich in reactive sites such as amino, epoxy, hydroxyl, and carboxyl (-COOH) groups, which is beneficial for subsequent coupling and immobilization of proteins, antibodies, metal chelates, ion exchange groups, or hydrophobic ligands on the microspheres.

[0012] Preferably, in S1, the concentration of the styrene-maleic anhydride copolymer or its derivative is 1% to 10% (w / v), for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%; the number-average molecular weight (Mn) is 1000 to 50000, for example, 1000, 3000, 5000, 8000, 10000, 20000, 30000, 40000, or 50000; the molar content of maleic anhydride is 20% to 50%, for example, 20%, 25%, 30%, 35%, 40%, 45%, or 50%; and the derivative is an esterified derivative, an amidated derivative, a sulfonated derivative, or a multi-component copolymer based on styrene-maleic anhydride.

[0013] Optimizing the number-average molecular weight of SMA and the molar content of maleic anhydride ensures good permeability and high reactivity. Molecular weight significantly impacts the coating structure. Excessively high molecular weight increases viscosity, affecting its distribution within the microsphere pores and potentially causing pore blockage. Conversely, excessively low molecular weight leads to shorter chain lengths and larger inter-chain gaps, affecting the formation and strength of the three-dimensional network structure. Maleic anhydride groups are the primary active groups; higher content results in a higher density of active groups. However, since it is an alternating copolymer with styrene, its maximum content generally does not exceed 50%. Insufficient content leads to poor stability of the subsequent coating.

[0014] Preferably, the styrene-maleic anhydride-based multi-component copolymer is a styrene-maleic anhydride-acrylate terpolymer, a styrene-methyl methacrylate-maleic anhydride terpolymer, a pentaerythritol stearate-styrene-maleic anhydride terpolymer, a styrene-N-phenylmaleimide-maleic anhydride terpolymer, or a styrene-maleic anhydride-octadecylamine terpolymer; and the esterified derivative is SMA-gO-3, SMA-gO-6, SMA-gO-10, SMA-gO-15, and SMA-gO-20.

[0015] In S1, the organic solvent is selected from one or more of ethyl acetate, butyl acetate, and dioxane. These solvents have good solubility for SMA and low swelling of subsequent matrix microspheres.

[0016] In S1, stirring is preferably carried out at 40°C to 70°C, and most preferably at 50°C to 60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, and 60°C.

[0017] In S1, the concentration of SMA or its derivatives ranges from 1% to 10% (w / v), which is adjusted according to the porosity of the target microspheres and the required coating thickness. For products with high porosity, low microsphere strength and high coating thickness requirements, the concentration of SMA or its derivatives can be increased to 5% to 10%, while for products with low porosity, high microsphere strength and low coating thickness requirements, the concentration of SMA or its derivatives can be adjusted to 1% to 5%.

[0018] In S2, the matrix microspheres can be non-porous or porous. Porous matrix microspheres are preferred, including polymethacrylate microspheres (PMA), polystyrene-divinylbenzene microspheres (PS-DVB), cross-linked agarose microspheres, silica microspheres, dextran microspheres, polyacrylamide microspheres, polymethacrylamide microspheres, poly(hydroxyalkyl vinyl ether) microspheres, poly(hydroxyalkyl acrylate) microspheres, or their hydrophilicized modified products.

[0019] Preferably, in S2, a vacuum of -0.05 to -0.3 MPa is maintained, for example, -0.05 MPa, -0.1 MPa, -0.15 MPa, -0.2 MPa, -0.25 MPa, or -0.3 MPa, to ensure that the SMA or its derivative solution is fully diffused and adsorbed on the entire inner and outer surfaces and pores of the microspheres.

[0020] In S2, the solid-liquid ratio (w / v) of the microspheres to the solution is preferably 1:1 to 4, for example, it can be 1:1, 1:2, 1:3, or 1:4.

[0021] In S2, it is preferable to stir at 40℃ ~ 70℃ for 0.5 ~ 1 h.

[0022] Preferably, in S3, when the physical adsorption is the π-π conjugation between the benzene ring in the styrene-maleic anhydride copolymer or its derivative and the benzene ring on the surface of the microspheres, after forming the coating layer, 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30, CAS: 90-72-2), imidazole or its derivative, and pyridine or its derivative are added as catalysts for the next step.

[0023] For microspheres containing benzene rings, such as the anchoring of SMA or its derivatives in PS-DVB matrix microspheres: After continuous stirring at 40℃~70℃ for 1~6 h, preferably 2~4 h, the benzene rings on the surface of the PS-DVB microspheres and the benzene rings in the SMA or its derivative molecules are bonded together through π-π conjugation (physical adsorption), forming a stable coating layer. After coating, the aforementioned catalyst can be added. These catalysts do not react in the anchoring step, facilitating the subsequent curing process. The catalyst includes imidazole or its derivatives such as imidazole, 2-methylimidazole, and 2-ethyl-4-methylimidazole; and pyridine or its derivatives such as pyridine, 4-dimethylaminopyridine, and 2,6-dimethylpyridine.

[0024] Preferably, in step S3, when the chemical reaction involves the reaction of the anhydride in the styrene-maleic anhydride copolymer or its derivative with the epoxy groups on the surface of the microspheres, 2,4,6-tris(dimethylaminomethyl)phenol, imidazole, or their derivatives are added as catalysts; when reacting with the hydroxyl groups on the surface of the microspheres, pyridine or its derivatives are added as catalysts. The imidazole or its derivatives include imidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, etc. The pyridine or its derivatives include pyridine, 4-dimethylaminopyridine, 2,6-dimethylpyridine, etc.

[0025] For microspheres containing epoxy groups on their surface, such as the anchoring of SMA or its derivatives in PMA matrix microspheres: DMP-30, imidazole or its derivatives are added to the system as catalysts, and the reaction is maintained at 40℃ ~ 70℃ for 6 h ~ 8 h. The catalyst can lower the activation energy of the system reaction, allowing the anhydrides on the SMA or its derivative molecules to react with the epoxy groups on the surface of the PMA microspheres at a lower temperature, thereby anchoring the SMA or its derivatives on the surface of the PMA matrix microspheres and forming a coating layer.

[0026] For microspheres containing hydroxyl groups on their surface, such as SMA or its derivatives anchored on agarose matrix microspheres: Pyridine or its derivatives are added to the system as a catalyst, and the reaction is maintained at 40℃ to 70℃ for 6 h to 8 h. This allows the anhydrides on the SMA or its derivative molecules to react with the hydroxyl groups on the agarose surface at a lower temperature, thus anchoring the SMA or its derivatives on the surface of the agarose matrix microspheres to form a coating layer.

[0027] Preferably, in S4, the crosslinking agent is a diamine, a diol, or a diepoxy group.

[0028] A diamine crosslinking agent is added to the anchored coating system, and the reaction is continued at 40℃ to 70℃ for 6 to 12 hours. The remaining anhydrides in the SMA or its derivatives can undergo intermolecular and intramolecular crosslinking reactions through the diamine, forming a crosslinked network support structure with amide groups as nodes. The resulting microspheres are suitable for systems with a pH of 4 to 12. The preferred diamine crosslinking agent is a short-chain diamine such as ethylenediamine, propylenediamine, or butylenediamine.

[0029] Add a diol or diepoxy crosslinking agent to the anchored coating system and maintain the temperature at 40°C to 70°C for 6 to 12 hours. The remaining anhydride in the SMA or its derivatives can undergo intermolecular and intramolecular crosslinking reactions through the diol or diepoxy group to form a crosslinked network support structure with ester groups as nodes. The resulting microspheres are suitable for systems with pH 4 to 9. The preferred diol or diepoxy crosslinking agent is a short-chain diol or diepoxy compound such as ethylene glycol, propylene glycol, butanediol, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,2-cyclohexanediol diglycidyl ether, di(2-epoxypropyl) ether, or dipropylene glycol diglycidyl ether.

[0030] Preferably, in S1 to S4, the temperature is maintained at 40°C to 70°C.

[0031] In S5, it is preferable to wash thoroughly with 0.5 M sulfuric acid, 0.2 M sodium hydroxide, and purified water to completely remove unreacted SMA or its derivatives, crosslinking agents, catalysts, and byproducts, thereby obtaining surface-modified microspheres.

[0032] The present invention also provides microspheres prepared by the method described above.

[0033] This invention also provides the application of the microspheres in the preparation of chromatographic media, wherein the chromatography includes affinity chromatography, ion exchange chromatography, hydrophobic interaction chromatography, reversed-phase chromatography, chelation chromatography, or covalent chromatography. The microspheres prepared by this method can be used for coupling and immobilizing proteins, antibodies, metal chelates, ion exchange groups, or hydrophobic ligands.

[0034] Beneficial Effects: Compared with existing technologies, this invention has the following significant advantages: 1. This method can enhance the mechanical strength and surface functionalization of microspheres without altering their original morphology and pore size distribution. The enhancement effect is uniform and does not clog the pores. The resulting microspheres possess excellent compressive strength, improved chemical stability, and abundant subsequent coupling reaction sites. 2. This method is applicable to various chromatographic media microspheres, exhibiting good versatility and facilitating the rapid preparation of various high-performance chromatographic media, adsorbents, or drug carriers. Attached Figure Description

[0035] Figure 1 SEM image of the PS-DVB matrix porous microspheres coated with reinforcement in Example 1;

[0036] Figure 2 This is the load test spectrum for Example 2;

[0037] Figure 3 This is the load test spectrum for Example 4;

[0038] Figure 4 The load test spectrum is shown in Comparative Example 1.

[0039] Figure 5 This is the load test spectrum for Example 3;

[0040] Figure 6 The load test spectrum is shown in Comparative Example 2.

[0041] Figure 7 The pressure versus linear velocity curves for the agarose matrix (Example 3 and Comparative Example 2). Detailed Implementation

[0042] The technical solution of the present invention will be further described below with reference to the accompanying drawings.

[0043] Example 1

[0044] This embodiment provides a method for modifying PS-DVB microspheres with a styrene-maleic anhydride copolymer, the steps of which are as follows:

[0045] (1) Dissolve 0.5 g of low molecular weight styrene-maleic anhydride copolymer SMA (Mn=1700, maleic anhydride MAH content 30%) in 50 mL of ethyl acetate and heat and stir at 55°C to dissolve.

[0046] (2) Add 12.5 g of porous PS-DVB microspheres (particle size 50 μm, pore size 30 nm), and stir and soak for 3 h at -0.05 MPa and 55℃.

[0047] (3) Add 0.01 g of 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) to the system, and then slowly add 0.15 g of ethylenediamine. React for 6 h.

[0048] (4) Filter and wash with ethanol, 0.5 M sulfuric acid, 0.2 M sodium hydroxide and purified water to obtain modified PS-DVB microspheres.

[0049] Example 2

[0050] This embodiment provides a method for modifying PMA microspheres with a styrene-maleic anhydride copolymer, the steps of which are as follows:

[0051] (1) Dissolve 1 g of styrene-maleic anhydride copolymer SMA (Mn=5000, maleic anhydride MAH content 50%) in 50 mL of ethyl acetate and heat and stir at 55°C to dissolve.

[0052] (2) Add 15 g of porous PMA microspheres (particle size 60 μm, pore size 80 nm), and stir and soak for 1 h at -0.05 MPa and 55 °C.

[0053] (3) Add 0.03 g of 4-dimethylaminopyridine (DMAP) to the system and maintain the reaction at 55°C for 6 h.

[0054] (4) Add 0.2 g of ethylene glycol diglycidyl ether to the system and continue the reaction at 55°C for 8 h.

[0055] (5) Finally, filter and wash with ethanol, 0.5 M sulfuric acid, 0.2 M sodium hydroxide and purified water to obtain modified PMA microspheres.

[0056] The hydrophobic ligand is further coupled to the obtained microspheres, as follows:

[0057] (1) 10 g of coated and modified PMA-based spheres were washed with 2 times the volume of 0.5 M sulfuric acid at room temperature for 2 h. After washing and filtration, they were mixed with 27.8 g of purified water and 1.5 g of sodium hydroxide. Then 94 g of glycerol glycidyl ester was added, and the reaction was kept at the temperature for 10 h. After washing with water until neutral, the grafted PMA microspheres were obtained.

[0058] (2) The grafted PMA microspheres were washed with 2 times the volume of 0.5 M sulfuric acid at room temperature for 2 h. After washing and filtration, they were mixed evenly with 27.8 g purified water and 1.5 g sodium hydroxide. Then 70 g butyl glycidyl ether was added to obtain hydrophobic PMA matrix filler.

[0059] Example 3

[0060] This embodiment provides a method for modifying agarose microspheres with a styrene-maleic anhydride copolymer, the steps of which are as follows:

[0061] (1) Dissolve 0.8 g of styrene-maleic anhydride copolymer SMA (Mn=2500, maleic anhydride MAH content 40%) in 40 mL of ethyl acetate / dioxane (volume ratio 7:3) mixed solvent and heat to 50 °C to dissolve completely.

[0062] (2) Add 10.0 g of cross-linked 6% agarose microspheres and gently stir for 1 h at -0.05 MPa and 50°C.

[0063] (3) Add 0.03 g of pyridine and continue the reaction at 50°C for 6 h.

[0064] (4) After the reaction is complete, slowly add 0.1 g of 1,4-butanediol and continue to maintain the reaction at 50°C for 8 hours.

[0065] (5) Finally, filter and wash with ethanol, 0.5 M sulfuric acid, 0.2 M sodium hydroxide and purified water to obtain modified agarose microspheres.

[0066] The following steps are taken to further couple ligands to the obtained microspheres:

[0067] (1) Mix 10.0 g of modified agarose microspheres, 27.8 g of purified water and 1.5 g of sodium hydroxide evenly, then heat the system to 35°C, add 94 g of glycerol triglycidyl ester, keep the reaction at the temperature for 10 h, and then wash with purified water until neutral to obtain grafted agarose microspheres.

[0068] (2) The grafted agarose microspheres were mixed with 33.4 g of purified water and 2.0 g of sodium chloride. Then, 30 L of 30% trimethylamine aqueous solution was added dropwise. After the addition was completed, the reaction was carried out at room temperature for 12 h. The packing was then washed with purified water to obtain anionic agarose packing.

[0069] Example 4

[0070] This embodiment is basically the same as Example 2, except that it uses an acrylate-styrene-maleic anhydride terpolymer (molar ratio of 1:2:2) with a molecular weight of 5000.

[0071] Example 5

[0072] This embodiment is basically the same as Embodiment 2, except that 1 g of styrene-maleic anhydride copolymer SMA (Mn=5000, maleic anhydride MAH content 50%) is replaced with 5 g of styrene-maleic anhydride copolymer SMA (Mn=50000, maleic anhydride MAH content 50%), while other aspects remain unchanged.

[0073] Comparative Example 1

[0074] The method of coupling hydrophobic ligands in Comparative Example 1 and Example 2 is basically the same, except that PMA microspheres without SMA modification were used. The steps are as follows.

[0075] 1. 10 g of porous PMA microspheres (particle size 60 μm, pore size 80 nm) were washed with 2 volumes of 0.5 M sulfuric acid at room temperature for 2 h. After washing and filtration, the microspheres were mixed with 27.8 g of purified water and 1.5 g of sodium hydroxide. Then 94 g of glycerol glycidyl ester was added and the mixture was kept at the temperature for 10 h. After washing with water until neutral, the grafted PMA microspheres were obtained.

[0076] 2. The grafted PMA microspheres were washed with 2 times the volume of 0.5 M sulfuric acid at room temperature for 2 h. After washing and filtration, they were mixed with 27.8 g of purified water and 1.5 g of sodium hydroxide. Then, 70 g of butyl glycidyl ether was added to obtain hydrophobic PMA matrix filler.

[0077] Comparative Example 2

[0078] The method of coupling ligands in Comparative Example 2 and Example 3 is basically the same, except that unmodified agarose microspheres were used. The steps are as follows.

[0079] 1. Mix 10.0 g of cross-linked 6% agarose microspheres, 27.8 g of purified water and 1.5 g of sodium hydroxide evenly, then heat the system to 35°C, add 94 g of glycerol triglycidyl ester, keep the reaction at this temperature for 10 h, and then wash with purified water until neutral to obtain grafted agarose microspheres.

[0080] 2. The grafted agarose microspheres were mixed with 33.4 g of purified water and 2.0 g of sodium chloride. Then, 30 L of 30% trimethylamine aqueous solution was added dropwise. After the addition was completed, the reaction was carried out at room temperature for 12 h. The packing material was then washed with purified water to obtain anionic agarose packing material.

[0081] Performance testing:

[0082] 1. The modified PS-DVB microspheres of Example 1 were taken and their appearance and pore structure were observed using a Zeiss EVO 10 electron microscope scanner.

[0083] 2. The dynamic loading capacity of the hydrophobic PMA matrix packing was tested by HPLC.

[0084] Test conditions: The chromatography column was a 4.6×50 mm stainless steel column, the column temperature was 25℃, the flow rate was 1 mL / min, the detection wavelength was UV280 nm, the test sample was lysozyme, and the instrument was an Agilent 1260 Infinity II.

[0085] Mobile phase preparation: Mobile phase A is 2 M ammonium sulfate + 25 mM PB, pH 7.0; Mobile phase B is 25 mM PB, pH 7.0; Sample loading solution C is a 1 g / L solution of lysozyme and mobile phase A.

[0086] Test method: First, equilibrate the column with mobile phase A, then replace the mobile phase in the system with sample solution C until the replacement is complete. Continue to use sample solution C as the mobile phase to plot the flow-through curve until the curve flattens out. Take the time at 10% breakthrough point to calculate the loading.

[0087] 3. The dynamic loading capacity of anionic agarose packing material was determined by HPLC.

[0088] Test conditions: The chromatography column was a 6.6×150 mm glass column, the column temperature was 25℃, the flow rate was 2.5 mL / min, the detection wavelength was UV280 nm, the test sample was BSA, and the instrument was an Agilent 1260 Infinity II.

[0089] Mobile phase preparation: Mobile phase A is 50 mM Tris, pH 8.5; Mobile phase B is mobile phase A + 0.5M sodium chloride, pH 8.5; Sample loading solution C is a 2 g / L solution prepared from mobile phase A.

[0090] Test method: Wash with mobile phase B until the baseline is stable, then equilibrate the column with mobile phase A, then replace mobile phase A with sample solution C, and then plot the flow-through curve until the curve flattens out. Calculate the loading at 10% breakthrough time.

[0091] 4. The pressure of anionic agarose packing material was tested using FPLC.

[0092] Test conditions: A 10 mm × 200 mm glass column was used at a column temperature of 25℃. The flow rate was increased by a linear velocity gradient of 50 cm / h. The mobile phase was 0.1 M sodium chloride. The instrument was a SCG-030 from Saipu Technology.

[0093] Test method: Use 0.1 M NaCl solution as the mobile phase and employ a gradient flow rate method (increase the flow rate by 50 cm / h every 5 min). Maintain this flow rate until the column bed stabilizes when the column pressure difference is 3 bar. Record the position of the column bed (the column bed height should be 20 cm). Screw the upper column head sieve plate to the corresponding position. After the column is packed, switch the mobile phase to deionized water and test using an FPLC system. Use the gradient flow rate method (increase the flow rate by 50 cm / h every 5 min) to obtain the maximum flow rate at the specified pressure and plot the pressure-flow rate curve.

[0094] Test results: Figure 1 Images of the appearance and pores of the coated PS-DVB microspheres are shown, indicating that coating with SMA or its derivatives does not cause microsphere deformation or pore blockage. Figure 2 , 3 and Figure 4 The loading test curves of Examples 2, 4 and Comparative Example 1 are shown. The loading of the modified PMA matrix hydrophobic filler is significantly higher than that of the unmodified matrix spheres, indicating that there are more active sites after coating, which can be used to prepare some products with high ligand density. Figure 5 and Figure 6 The same conclusion was confirmed for the modified agarose-based anionic filler; and Figure 7 The pressure of the packing material at different linear velocities is shown. A higher linear velocity and lower pressure indicate stronger pressure resistance of the packing material. As can be seen from the figure, the modified agarose matrix packing material exhibits significantly lower pressure at the same linear velocity, indicating that coating with SMA or its derivatives can effectively enhance the pressure resistance of the substrate. Loading test data for the examples and comparative examples are shown in Table 1.

[0095]

Claims

1. A method for modifying microspheres with a styrene-maleic anhydride copolymer or its derivative, characterized in that, A coating of styrene-maleic anhydride copolymer or its derivatives is formed on the surface of microspheres by physical adsorption or chemical reaction, and then a crosslinking agent is used to form a network structure in the coating.

2. The method according to claim 1, characterized in that, Includes the following steps: S1: Dissolution of styrene-maleic anhydride copolymer or its derivatives: Dissolve styrene-maleic anhydride copolymer or its derivatives in an organic solvent and heat and stir until a homogeneous and transparent solution is formed; S2: Microsphere wetting: Add the matrix microspheres to the solution obtained in S1 and stir continuously; S3: Styrene-maleic anhydride copolymer or its derivatives anchored: Styrene-maleic anhydride copolymer or its derivatives are anchored on the surface of microspheres by physical adsorption or chemical reaction to form a coating layer; S4: Coating curing: Add a crosslinking agent to the anchored coating system to form a crosslinked network support structure; S5: Post-processing: Separate the microspheres by filtration or centrifugation, and wash to obtain the modified microspheres.

3. The method according to claim 2, characterized in that, In S1, the concentration of the styrene-maleic anhydride copolymer or its derivative is 1% to 10% (w / v), the number average molecular weight is 1,000 to 50,000, and the molar content of maleic anhydride is 20% to 50%; the derivative is an esterified derivative, an amidated derivative, a sulfonated derivative, or a multi-component copolymer based on styrene-maleic anhydride.

4. The method according to claim 3, characterized in that, The styrene-maleic anhydride-based multi-component copolymers are styrene-maleic anhydride-acrylate terpolymer, styrene-methyl methacrylate-maleic anhydride terpolymer, pentaerythritol stearate-styrene-maleic anhydride terpolymer, styrene-N-phenylmaleimide-maleic anhydride terpolymer, and styrene-maleic anhydride-octadecylamine terpolymer; the esterified derivatives are SMA-gO-3, SMA-gO-6, SMA-gO-10, SMA-gO-15, and SMA-gO-20.

5. The method according to claim 2, characterized in that, In S2, the matrix microspheres are porous matrix microspheres, including polymethacrylate microspheres, polystyrene-divinylbenzene microspheres, cross-linked agarose microspheres, silica microspheres, dextran microspheres, polyacrylamide microspheres, polymethacrylamide microspheres, poly(hydroxyalkyl vinyl ether) microspheres, poly(hydroxyalkyl acrylate) microspheres, or their hydrophilic modified products.

6. The method according to claim 2, characterized in that, In step S3, when the physical adsorption is achieved by the benzene ring in the styrene-maleic anhydride copolymer or its derivative undergoing π-π conjugation with the benzene ring on the surface of the microspheres, after forming a coating layer, 2,4,6-tris(dimethylaminomethyl)phenol, imidazole or its derivative, and pyridine or its derivative are added as catalysts for the next step.

7. The method according to claim 2, characterized in that, In S3, when the chemical reaction is the reaction between the anhydride in the styrene-maleic anhydride copolymer or its derivative and the epoxy groups on the surface of the microspheres, 2,4,6-tris(dimethylaminomethyl)phenol, imidazole or their derivatives are added as catalysts; when reacting with the hydroxyl groups on the surface of the microspheres, pyridine or its derivatives are added as catalysts.

8. The method according to claim 2, characterized in that, In S4, the crosslinking agent is a diamine, a diol, or a diepoxy group.

9. A microsphere prepared by the method according to any one of claims 1-8.

10. The application of the microspheres according to claim 9 in the preparation of chromatographic media, characterized in that, The chromatography includes affinity chromatography, ion exchange chromatography, hydrophobic interaction chromatography, reversed-phase chromatography, chelation chromatography, or covalent chromatography.